Laser Measurement Technology: Fundamentals and Applications - Donges, Axel (Springer, 2016)
Laser measurement technology has evolved in the last years in a versatile and reflationary way. Today, its methods are indispensable for research and development activities as well as for production technology. Every physicist and engineer should therefore gain a working knowledge of laser measurement technology.